Analysis of nortriptyline's prophylaxis on hemodialysis headache patients - a pilot study - Lima, Bruna Mendonça; Santos, Paulo Sergio Faro; Jesus, Alan Chester Feitosa de (Headache Medicine, 2016)
Background: Headache is the most common neurological symptom of patients on hemodialysis treatment. However, this condition is usually treated only after the pain has already begun. Objective: Determine the efficacy and tolerability of nortriptyline as a prophylactic treatment for patients diagnosed with hemodialysis headache. Methods: This study is an open and a prospective clinical trial. Twelve patients with hemodialysis headache were studied in this trial. They were asked to take nortriptyline (25 mg per day) during three months as a prophylaxis for their headaches. Weekly interviews were made to register eventual headaches. Additionally, other clinical features were analyzed such as the intensity of pain, its location, side effects of the drug and use of abortive medications. Results: There was a significant reduction (p < 0.05) in the intensity as well as frequency of pain. The duration of the episodes also decreased. Conclusions: Our findings suggest that nortriptyline 25 mg is capable of reducing not only the frequency, but also the intensity of the pain in the hemodialysis headache. However, further studies are necessary.